Exploring the Usage of Emotional Skills Development in the Poetry of Rajab Ibrahimi - Stanikzai, Sultan Mohammad; Kalon, Abdul Wahid; Maroofi, Safiullah (Journal Corner of Education, Linguistics, and Literature, 2024)
This study explores the use of emotional skills development in the poetry of Rajab Ibrahimi, a significant contemporary Persian poet known for his profound emotional expressions. The objective is to analyze how Ibrahimi employs emotional skills such as empathy, self-awareness, and emotional regulation to enhance the reader's connection to the themes of love, loss, and resilience within his work. Utilizing a qualitative methodology, the research involves closely reading selected poems, focusing on language, imagery, and thematic elements that illustrate emotional complexity. The analysis reveals that Ibrahim’s poetry not only articulates personal feelings but also catalyzes readers to engage in emotional reflection and growth. Specific examples highlight how his nuanced use of metaphor and symbolism fosters empathy, inviting readers to explore their emotional landscapes. The findings suggest that Ibrahim’s work has significant pedagogical implications; it can be utilized in educational contexts to promote emotional intelligence and skills development. Ultimately, the study concludes that Rajab Ibrahim’s poetry transcends artistic expression, offering a vital platform for emotional awareness and development, thus enriching the discourse on the interplay between literature and emotional skill cultivation.